Firing Costs and Flexibility: Evidence from Firms' Employment Responses to Shocks in India - Adhvaryu, Achyuta; Chari, A. V.; Sharma, Siddharth (The Review of Economics and Statistics, 2013)
A key prediction of dynamic labor demand models is that firing restrictions attenuate firms' employment responses to economic fluctuations. We provide the first direct test of this prediction using data from India. We exploit the fact that rainfall fluctuations, through their effects on agricultural productivity, generate variation in local demand within districts over time. Consistent with the theory, we find that industrial employment is more sensitive to shocks where labor regulation is less restrictive. Our results are robust to controlling for endogenous firm placement and vary across factory size in a pattern consistent with institutional features of Indian labor law.